Development of the Methodological Proposals for the Use of Innovative Risk-Based Mechanism in Transport System - Piterska, Varvara; Shakhov, Anatoliy; ., . (International Journal of Engineering and Technology, 2018)
It can be concluded that the system of analysis and risk management is an effective mechanism for accelerating of customs clearance and improving of the quality of customs control in the functioning of the transport system. The proposed risk management mechanism for performing customs and technological procedures within the transport system reflects a sequence of actions that involves selecting one or more monitoring objects for careful analysis and determination of risk indicators, followed by a decision on the use of forms and methods of customs control, taking into account the probability the occurrence of potential or real loss. The use of the proposed methodology will significantly shorten the time of customs procedures, and therefore, reduce the time of transportation of goods across the border, exclude the downtime of transports through the implementation of simplified controls taking into account the requirements of the World Trade Organization, as well as the integrated use of the Kyoto Convention on the basis of assessing of the loss from the risk situation.